Being a Teacher-researcher in Indonesia: Understanding the Motivational Factors of In-service ELT Teachers - Handayani, Ellisa Indriyani Putri; Drajati, Nur Arifah; Cahyaningrum, Dewi; Handayani, Anis (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Conducting research may contribute positively to teachers’ professionalism and maintain their Career-Long Professional Learning (CLPL). However, many teachers find it challenging and hesitant to conduct research. In this regard, this descriptive quantitative study compares novice and experienced teachers’ motivational factors affecting their decision to conduct research despite their other responsibilities as teachers. This study involved 127 English language teachers who are also active researchers. The data were obtained by using an online survey adopting the Teacher Research Motivation Scale (TRMS) proposed by Hosseini & Bahrami (2022) consisting of 22 items. Descriptive statistics and Mann U-Whitney test were then performed using SPSS software to identify the differences between novice and experienced teachers in their research motivation. The results mostly highlight the importance of comprehensively understanding in-service teachers’ motivational factors to conduct research and foster their willingness to be actively involved in research projects. Government and other educational practitioners may reflect on this study’s result to encourage teachers to conduct research and maintain their professionalism in teaching.